Identifying and unlocking the value from heat decarbonisation in the United Kingdom. (July 2022) - Daruwala, Abbas; Workman, Mark; Hardy, Jeffrey
Abstract: Decarbonisation of heat is critical to the UK achieving its net zero emissions target by 2050. With the low rate of asset turn-over in the heat sector, decarbonisation needs to start immediately. However, the risk and uncertainty regarding the most 'cost optimal pathway' across the range of technology options and the lack of a holistic UK heat policy is failing to provide a clear directive as to how market actors should address UK heat decarbonisation. This research applies a novel commercial perspective to provide additional insight beyond that which traditional cost optimal tools are able to offer. The value pool approach is used to determine the magnitude of economic opportunities and map their resilience across multiple net zero scenarios in decadal timesteps to 2050. Our work indicates that by 2050 an annual value of £28 billion potentially exists in decarbonising heat in the UK. Realising this value, however, is subject to significant path-dependency. Unlocking the value will require substantial additional policy and regulatory support, business model innovation and unprecedented levels of consumer engagement and protection in the history of the energy sector.